24 synoptic maps 1974-1982 (ascending phase of cycle XXI) of 323 prominence average magnetic fields measured by the Hanle effect. Issue Volume 8:Issue S300(2013) (6th January 2014) - Bommier, Véronique
Abstract: The poster was made of 323 average prominence magnetic fields reported on 24 synoptic maps. The paper first resumes the methods for the field derivation, and the different results of the whole program of these second generation Hanle effect observations. From their conclusions, it was possible to derive a unique field vector for each of the 323 prominences. The maps put in evidence a large scale structure of the prominence magnetic field, probably distorted by the differential rotation, which leads to a systematically small angle (on the order of 30°) between the field vector and the prominence long axis.